Construction of an Antibiotic-Free Vector and its Application in the Metabolic Engineering of Escherichia Coli for Polyhydroxybutyrate Production - Liao, Ying-Cheng; Saengsawang, Boonyawee; Chen, Jun-Wei; Zhuo, Xiao-Zhen; Li, Si-Yu (Frontiers in Bioengineering and Biotechnology, 2022)
An antibiotic- and inducer-free culture condition was proposed for polyhydroxybutyrate (PHB) production in recombinant Escherichia coli. First, antibiotic-free vectors were constructed by installing the plasmid maintenance system, alp7, hok/sok, and the hok/sok and alp7 combination into the pUC19 vector. The plasmid stability test showed that pVEC02, the pUC19 vector containing the hok/sok system, was the most effective in achieving antibiotic-free cultivation in the E. coli B strain but not in the K strain. Second, the putative phaCAB operon derived from Caldimonas manganoxidans was inserted into pVEC02 to yield pPHB01 for PHB production in E. coli BL21 (DE3). The putative phaCAB operon was first shown function properly for PHB production and thus, inducer-free conditions were achieved. However, the maintenance of pPHB01 in E. coli requires antibiotics supplementation. Finally, an efficient E. coli ρ factor-independent terminator, thrLABC (ECK120033737), was inserted between the phaCAB operon and the hok/sok system to avoid possible transcriptional carry-over. The newly constructed plasmid pPHB01-1 facilitates an antibiotic- and inducer-free culture condition and induces the production of PHB with a concentration of 3.0 on0.2 g/L, yield of 0.26 /L0.07 g/g-glucose, and content of 44 /g3%. The PHB production using E. coli BL21 (DE3)/pPHB01-1 has been shown to last 84 and 96 h in the liquid and solid cultures.